(untitled) (Research, Society and Development, 2022)
Visceral leishmaniasis in Brazil is caused by a protozoan, commonly Leishmania infantum, transmission occurs by blood repast of females of the vector insect, the phlebotomine. This disease is of relevant impact to public health, dogs are considered reservoirs and flags of the existence of infected sandbumbotoines. Thus, the objective was to diagnose visceral leishmaniasis in sergipano sertão dogs and to evaluate the perception of dog and cat tutors regarding this disease. An epidemiological study of the analytical, observational and cross-sectional type was performed. Being made the diagnosis of visceral leishmaniasis of dogs treated at the outpatient clinic of the Sertão Campus of the Federal University of Sergipe and interviews with the tutors of dogs and cats in the 2020 rabies vaccination campaign, in the municipality of Nossa senhora da Glória, Sergipe. Regarding the diagnosis, 3.33% of the dogs tested were reagents. Female tutors (71%), aged 26 to 49 years (52%), 29% completed high school and 45% with family income below 1 minimum wage were interviewed. Of the interviewees who reported knowing the disease, 23% knew it through health professionals and 56% stated that visceral leishmaniasis is a zoonosis, but they are unaware of transmission and prevention. In view of the data obtained, it is noticed that a large part of the population does not know basic information about visceral leishmaniasis, and health education actions are necessary.